Necrotizing Sarcoid Granulomatosis: A Disease Not to be Forgotten - Parejo-Morón, A. I. (Case Rep Med, 2020)
Sarcoidosis is a systemic granulomatous disease of unknown aetiology characterised by the appearance of noncaseifying epithelioid granulomas in the affected organs, most commonly the lungs, skin, and eyes (Iannuzzi et al. 2007). Necrotizing Sarcoid Granulomatosis (NGS) is a rare and little-known form of disease, which also presents nodular lung lesions, and it shares pathologic and clinical findings with sarcoidosis, where the presence of necrosis may lead to misdiagnosis of tuberculosis (TB), leading to a consequent delay in treatment of the underlying entity (Chong et al. 2015). This is exactly what happened with the two cases that we present here.